PERANCANGAN SISTEM INFORMASI LAYANAN DINAS PERDAGANGAN BERBASIS WEBSITE (Studi Kasus Dinas Perdagangan Kabupaten Nunukan Kalimantan Utara) - Theresyah Marshella (2022)
The Trade Service is one of the government agencies located in the Nunukan district of North Kalimantan which still does not have a website-based service information system so that it is difficult for other agencies and the public to know. The service information system can be used as a medium of information so that the information possessed is quickly accessed so that it is known by internal and external parties. Therefore, a website-based Service Information System for the Trade Service is needed. The purpose of this research is to help people who want to know information about the Department of Trade, make it easier for the Department of Trade employees to introduce the activities to be carried out, assist the Department of Trade in knowing the level of satisfaction of existing services, improve the performance of the trade office with this new information system, find out cost of basic materials, and provide knowledge about designing a website-based system using the PHP Framework Codeigniter programming language. In analyzing the needs of the author using the PIECES method and in designing the system the author uses the existing methods in the research flow. The results of this study are implementing a website-based service information system for the Trade Service.